Offene Kinder- und Jugendarbeit in Krisenzeiten aus Sicht von Jugendlichen Eine empirische Studie zur Bedeutung von Einrichtungen in Hamburg - Voigts, Gunda (Verlag Barbara Budrich, 2024)
Based on extensive data, including 800 hours of interview material, online questionnaires and group discussions, the second volume of results from the research transfer project "Child and Youth Work in Corona Times" at HAW Hamburg presents fascinating insights into the perspectives of young people between the ages of 13 and 25 on open child and youth work. The authors thus make a valuable contribution to the analysis of the significance of these institutions during the Corona era.